1 answer:
Answer:
x = - 3
y = - 2
Step-by-step explanation:
Start with the second equation. Switch
3y = 2x Divide by 3
3y/3 = 2x/3
y = 2x/3
Now go to the first equation. Put the value for y in the first equation.
x - 3(2x/3) = 3 Cancel the 3s on the left.
x - 2x = 3 Combine
-x = 3 Multiply by -1
-1(-x) = 3(-1)
x = - 3
Now go back to the original equation I have called the second equation
2x = 3y
2(-3) = 3y Put in - 3 for x
- 6 = 3y Divide by 3
-6 / 3 = y
y = - 2
You might be interested in
Answer:
The y axis
Step-by-step explanation:
Perpendicular means for a line to create a 90 degree angle, like it does on the y axis.
Hope this helps!
Answer:
6/3 I think so try c and if it’s not I’m not sure
Step-by-step explanation:
:)
Answer:
5/8
Step-by-step explanation:
40/64
20/32
10/16
5/8
yes it does have enough to cover the cube